PENDAMPINGAN PROGRAM KEMITRAAN PEMASARAN PRODUK HASIL PERIKANAN DI PONDOK PESANTREN SALAFIYAH SYAFI’IYAH SUKOREJO - Ramli Ramli (As-Sidanah, 2019)
Abstract: The assistance of fishery product marketing partnership program is intended as an effort for BUMP to utilize the market potential (offline market) of fishery products at the pondok pesantren Salafiyah Syafi'iyah Sukorejo and at the same time as an effort to increase market segmentation (offline market) of fishery products by UMKM Dapur Sehati. The time of activity is held from March to April 2019. The form of assistance is analyzing the market potential of fishery products at pondok pesantren, determining the superior fishery products processed based on the market potential analysis of pondok pesantren and the added value analysis of fishery products. The assistance results show that 1) The fishery products marketing partnership program at the pondok pesantren Salafiyah Syafi'iyah Sukorejo has resulted in interest from both partners, namely BUMP pondok pesantren Salafiyah Syafi'iyah Sukorejo with UMKM Dapur Sehati to collaborate although it has not reached the agreement on the two partners. 2) The initial product that can be developed and marketed is squid crackers. Squid crackers get a market good response at the pondok pesantren Salafiyah Syafi'iyah Sukorejo. Based on the added value analysis, the production of squid crackers gets an added value of Rp. 11,231,- per kilogram with a added value ratio of 41.60%, labor compensation of Rp. 1,500,- per kilogram of raw material, labor portion 13.36% of added value, profit of Rp. 9,731,- per kilogram and profit rate of 86.64% of added value.